Cardiac Function and Its Evolution with Pulmonary Vasodilator Therapy: A Myocardial Deformation Study. Issue 6 (26th March 2014) - Sehgal, Arvind; Ibrahim, Masitah; Tan, Kenneth
Mini‐Abstract Speckle tracking echocardiography–derived myocardial strain has useful clinical applications in adults with pulmonary hypertension (PH) as well as preterm infants with chronic lung disease. It is considered more sensitive compared to conventional indices. This report presents a 3‐month‐old infant with PH and poor right ventricular function who was treated with pulmonary vasodilator therapy. Impaired myocardial strain improved after inhaled nitric therapy. Strain analysis can help improve understanding of cardiac adaptation in critical clinical situations.